Life history of five small minnow mayflies (Ephemeroptera: Baetidae) in a small tropical stream on the Caribbean slope of Costa Rica - Vásquez, Danny (2009)
Life history characteristics of five species of Baetidae were investigated over a one-year period at Quebrada Gonza´ lez, a warmwater stream in Braulio Carrillo National Park. Larvae of three species of Baetodes and two species of Camelobaetidius were collected at monthly intervals. Measurements of head capsules show a wide size range within each species throughout the year. For all species studied, mature larvae with black wings pads were found during all months. Fecundity averaged less than 1000 eggs per female for all species. The asynchronous development, multiple overlapping cohorts, and long emergence period with reproduction occurring throughout the year suggest a multivoltine life history for all five species. The high water temperatures (annual mean 21.48C, ranging from 20.68C to 22.18C) throughout the year undoubtedly contribute to these life history patterns. The multivoltinism of these mayflies conforms to a general pattern of multivoltinism for aquatic insects in tropical regions.